Pendidikan Seni dan Kurikulum Merdeka Belajar: Tuntutan bagi Guru di Sekolah Dasar - Icuh Komala; Asep Nugraha (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2022)
Arts education underwent a curriculum change from Indonesia's Dutch occupation until Indonesia became independent and freed from the shackles of colonialism. The shift in the curriculum has continued until now. The newest curriculum in 2020 is the Freedom to Learn curriculum with the Pancasila Student Profile as its achievement. This article attempts to write down the journey of the existence of arts entities as learning content that is transmitted in schools in Indonesia and the implementation of the Merdeka Learning curriculum in the PGSD Study Program at Nusa Putra University. The aim is to provide an overview of the historical events of education in Indonesia, which are studied diachronically. The result found a synthesis that arts education has been applied and is always present in lessons in schools in Indonesia, including in the PGSD Study Program at Nusa Putra University, as a printer for prospective elementary school teachers by implementing the Merdeka Learning curriculum.